Crisis, enfermedad y poder en la iglesia cuadrangular Toba - Pablo Gerardo Wright (Estudios sobre las Culturas Contemporáneas)
The author describes and analyzes a case of encounter of cultural and religious perspectives in the presence of a critical situation: the illness of a comunal Toba leader. The divergence of religious/healing strategies and the symbolic convergence of its ends: to recover the communal political-symbolic order is shown.